Monetary theory and policy: The debate revisited - Jean Luc Gaffard (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This paper is aimed at revisiting monetary analysis in order to better understand erroneous choices in the conduct of monetary policy. According to the prevailing consensus, the market economy is intrinsically stable and is upset only by poor behaviour by government or the banking system. We maintain on the contrary that the economy is unstable and that achieving stability requires a discretionary economic policy. This position relies upon an analytical approach in which monetary and financial organisations are devices that help markets to function. In this perspective, which focuses on the heterogeneity of markets and agents, and, consequently, on the role of institutions in determining overall performance, it turns out that nominal rigidities and financial commitment offer the means to achieve economic stability. This is because they prevent successive, unavoidable disequilibria from becoming explosive.
Keywords: E31; E32; E5; E61; E62; 330; inflation; market; money; stability